Pain mechanisms in the spinal cord - Cervero, Fernando (Henry Stewart Talks, 2009)
Role of the spinal cord in pain processing, The dorsal horn of the spinal cord as a crossroads for pain transmission, Projection of primary sensory afferents to the spinal dorsal horn, Sensory outputs of the spinal cord, Classes of spinal cord neuron involved in pain processing, Role of the spinal cord in hyperalgesic states, Sensitization of spinal cord neurons, Descending modulation of pain transmission through the spinal cord